INDRALUPTA AND KESHAADA KRIMI A CASE STUDY - Bhagwat Pranav (International Journal of Applied Ayurved Research, 2016)
We often see our hair as a reflection of our identity because it is both personal and public. The deep personal relationship between hair and self-esteem is evident throughout history, philosophy and even religion. Alopecia areata is an autoimmune disorder also known as "spot baldness" that can be compared with Indralupta. Since the limitations of modern medicine are obvious, there is the highest need of harmless, effective treatment. Ayurveda indicates use of pracchana and lepa in the treatment. The treatment planned was prachhanna followed by maricha lepa. Raktamokshana is the ideal treatment when doshas are vitiated with rakta. Prachhanna helps in clearing the obstructed romakupas. Keshaada krumi associated in this case are also responsible for hair loss. As Keshaada are the krimis produced in raktavaahi sira samstha and are raktaja, their association indicates the use of internal krimighna chikitsa. The results shown were profound, quick and permanent and are an outstanding evi-dence of clinical application of principles of Ayurveda.